The Development of a Novel Direct-Expansion Ground Source Heat Pump (DE-GSHP) for Embankment Heating in Cold Regions - Mingxing Cao; Yimin Zhang; Tianfei Hu (Applied Sciences, 2023)
This study aimed to investigate the practical applications of a ground source heat pump (GSHP) system for heating applications in embankment engineering. A special direct-expansion GSHP (DE-GSHP) was designed and manufactured, and its performance was experimentally assessed. Subsequently, the newly developed DE-GSHP structure demonstrated an excellent heating performance with respect to positive heat-supplying temperatures in cold regions. The temperature could be automatically controlled at 30, 45, 60, and 75; additionally, the heat-absorbing temperatures were maintained below 0 °C, which was extremely lower than that of the deep frost-free stratum. Further, the experimental data were used to evaluate the coefficient of performance of the DE-GSHP, which was more than 3.5. The findings indicated that the GSHP has potential applications for embankment heating in cold regions.